DOI: 10.33612/diss.248380062
|View full text |Cite
|
Sign up to set email alerts
|

Exploration in red knots

Abstract: Chapter 1 is still unknown how the relation between the genes, epigenetic factors, maternal effects, and personal experiences affect the development of personality (Cabrera et al., 2021). Feedback between exploration and foraging behaviourForaging is essential for most organisms as it directly influences fitness. Individuals can differ in their methods of detecting prey (hereafter 'foraging tactics') if food items induce differences in the behaviours needed to collect them (e.g., Newsome et al., 2009).By forag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 201 publications
(368 reference statements)
0
0
0
Order By: Relevance
“…Such foraging habitat provides potential for local enhancement [6] as using social foraging information likely increases the chances of finding hidden food and ultimately the foraging success of the individual. A recent study, combining personality assays and high-throughput tracking, revealed that exploratory personality correlates with movement in the wild, and faster-exploring red knots visit more areas than slower explorers [31]. Thereby, faster explorers can find new foraging areas and provide foraging information to their conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…Such foraging habitat provides potential for local enhancement [6] as using social foraging information likely increases the chances of finding hidden food and ultimately the foraging success of the individual. A recent study, combining personality assays and high-throughput tracking, revealed that exploratory personality correlates with movement in the wild, and faster-exploring red knots visit more areas than slower explorers [31]. Thereby, faster explorers can find new foraging areas and provide foraging information to their conspecifics.…”
Section: Discussionmentioning
confidence: 99%